Additive Manufacturing of 3D Aerogels and Porous Scaffolds: A Review. (5th August 2021) - Tetik, Halil; Wang, Ying; Sun, Xiao; Cao, Daxian; Shah, Nasrullah; Zhu, Hongli; Qian, Fang; Lin, Dong
Abstract: Aerogels are highly porous structures produced by replacing the liquid solvent of a gel with air without causing a collapse in the solid network. Unlike conventional fabrication methods, additive manufacturing (AM) has been applied to fabricate 3D aerogels with customized geometries specific to their applications, designed pore morphologies, multimaterial structures, etc. To date, three major AM technologies (extrusion, inkjet, and stereolithography) followed by a drying process have been proposed to additively manufacture 3D functional aerogels. 3D‐printed aerogels and porous scaffolds showed great promise for a variety of applications, including tissue engineering, electrochemical energy storage, controlled drug delivery, sensing, and soft robotics. In this review, the details of steps included in the AM of aerogels and porous scaffolds are discussed, and a general frame is provided for AM of those. Then, the different postprinting processes are addressed to achieve the porosity (after drying); and mechanical strength, functionality, or both (after postdrying thermal or chemical treatments) are provided. Furthermore, the applications of the 3D‐printed aerogels/porous scaffolds made from a variety of materials are also highlighted. The review is concluded with the current challenges and an outlook for the next generation of 3D‐printed aerogels and porous scaffolds. Abstract : 3D‐printed aerogels and porous scaffolds made from a variety of materials have promising properties for electrochemical energy storage, electrical energy generation, sensors and soft actuators, biomedical, and environmental applications. This review discusses the details of 3D printing processes along with drying and other postprocesses. A comprehensive summary for applications is also provided.